Cohort size effects on wages, working status, and work time - Sarah Okoampah (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This paper estimates the effects of cohort size on wages, employment and work time for workers in Germany. The empirical findings suggest that male workers with medium and high degrees of occupational specialization who were born at the peak of the baby boom earn at least 5.3% lower wages than comparable workers born during the subsequent baby bust. Highly specialized females born into large cohorts earn 2.5% lower wages than their counterparts from small cohorts. Employment effects are detected only for highly specialized males. The effects on work time are mixed and invariably larger when actual work time is considered rather than contractual work time. It is argued that the restrictive labor market institutions in place are key in shaping the response pattern across the different economic outcomes. – – Dieses Papier schätzt Kohortengrößeneffekte auf Löhne, Beschäftigungswahrscheinlichkeiten und Arbeitszeiten für Arbeitnehmer in Deutschland. Die empirischen Ergebnisse implizieren, dass männliche Arbeiter in Berufen mit mittleren und hohen Spezialisierungsgraden aus den geburtenstärksten Jahrgängen des Babybooms mindestens 5,3% geringere Löhne haben als vergleichbare Arbeiter, die während der nachfolgenden geburtenschwachen Jahre geboren wurden. Hochspezialisierte Frauen aus großen Kohorten verdienen 2,5% geringere Löhne als vergleichbare Frauen aus kleinen Kohorten. Beschäftigungseffekte können nur für hochspezialisierte Männer nachgewiesen werden. Die geschätzten Arbeitszeiteffekte sind gemischt und stets größer, wenn tatsächliche anstelle von vertraglicher Arbeitszeit betrachtet wird. Es wird argumentiert, dass die bestehenden restriktiven Arbeitsmarktbeschränkungen eine Schlüsselgröße für das Reaktionsmuster zwischen verschiedenen Arbeitsmarktergebnissen darstellen.
Keywords: J21; J31; J11; 330; population aging; cohort size; labor market effects; labor market institutions